ANALISIS QUALITY PRODUCT, QUALITY PLACE, BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PADA PEH KOPI KEDIRI - Tiawan Putri, Verani Agus; Ichsannudin, Ichsannudin; Wihara, Dhiyan Septa (Universitas Nusantara PGRI Kediri, 2022)
This research aims to examine and analyze whether the variables of product quality, quality place, and brand image have an effect on purchasing decisions at Peh Kopi Kediri. The method used in this study is a quantitative approach using the type of causality associative research technique. The data was collected using a questionnaire which was distributed directly to 40 consumers of Peh Kopi Kediri using accidental sampling technique. This study was analyzed using classical assumption tests, multiple linear regression, and hypothesis testing with SPSS For Windows Version 21 software to process the data. This study found that the variables of product quality, quality place, and brand image had a positive and significant partial and simultaneous effect on purchasing decisions at Peh Kopi Kediri.